Model Pembelajaran Scramble Didukung Permainan Teka-Teki Silang Terhadap Kemampuan Mengidentifikasi Tokoh-Tokoh Sejarah Hindu-Budha di Indonesia - Ade Nur Ashari; Erwin Putera Permana; Muhamad Basori (STKIP PGRI SITUBONDO, 2022)
The influence of the scramble learning model supported by crossword puzzle games on the ability to identify Hindu-Budhist historical figures in Indonesia. The purpose of this study was to determine the ability to identify Hindu-Budhist historical figures in Indonesia using a scramble learning model supported by a crossword game. This type of reseach using an experimental design, namely pre-test and post-test groups. Data collection instruments used tests and data analysis techniques using normality test, homogeneity test, and hypothesis testing (using t test). based on the results of the analysis, there is an effect of using scramble learning models supported by crossword puzzle on the ability to identify Hindu-Buddhist historical figures in Indonesia. It is evident from t-count 9.090 > t-table 2.052 with a significance level of 0.00 < 0.05. Therefore, H0 and Ha are accepted, which means that there is a significant influence using the scramble learning model supported by crossword puzzle games on the ability to identify Hindu-Buddhist historical figures in Indonesia. Thus the use of scramble llearning models supported by crossword puzzle games can create fun and challenging learning for students. In learning, students are enthusiastic and active because each student tries to compete with other friends. In addition, the use of scramble learning models supported by crossword puzzle games also makes it easier for students to understand the material of Hindu-Budhhist historical figure in Indonesia.